(untitled) (Law and world, 2015)
The world has witnessed development and expansion of two distinct areas of international law wherein one deals with protection of human rights and the other with protecti on and promotion of foreign investment. Protection and promotion of foreign investment lies at very heart of numerous International Investment Agreements (IIAs). On the other hand, series of international treaties have been developed in response to the mandate set forth in the Charter of United Nations.1 The UN is empowered by the UN Charter to promote “higher standards of living, full enjoyment, and conditions of economic and social progress and development”,2 as well as “universal respect for, and observance of, human rights and fundamental freedoms for all without distinction as to race, sex, language, or religion”.